Neutrophils: a key component in ECMO-related acute organ injury - Zhang, Mingfu; Li, Shiping; Ying, Junjie; Qu, Yi (Frontiers in Immunology, 2024)
【Abstract】Extracorporeal membrane oxygenation (ECMO), as an extracorporeal life support technique, can save the lives of reversible critically ill patients when conventional treatments fail.However, ECMO-related acute organ injury is a common complication that increases the risk of death in critically ill patients, including acute kidney injury, acute brain injury, acute lung injury, and so on. In ECMO supported patients, an increasing number of studies have shown that activation of the inflammatory response plays an important role in the development of acute organ injury. Cross-cascade activation of the complement system, the contact system, and the coagulation system, as well as the mechanical forces of the circuitry are very important pathophysiological mechanisms, likely leading to neutrophil activation and the production of neutrophil extracellular traps (NETs). NETs may have the potential to cause organ damage, generating interest in their study as potential therapeutic targets for ECMO-related acute organ injury. Therefore, this article comprehensively summarized the mechanism of neutrophils activation and NETs formation following ECMO treatment and their actions on acute organ injury.